Collective labor agreement on deciding the deciding the disbursement of a special raise to the private sector workers in the year 2014 = اتفاقية عمل جماعية بشأن تقرير علاوة خاصة للعاملين بالقطاع الخاص لعام 2014. (2025)
Ministry of manpower and immigration collective labor agreement on deciding the disbursement of a special raise to the private sector workers in the year 2014 وزارة القوى العاملة والهجرة اتفاقية عمل جماعية بشأن تقرير علاوة خاصة للعاملين بالقطاع الخاص لعام 2014